ANALISIS PENGARUH HARGA, KUALITAS PRODUK, DAN KUALITAS LAYANAN TERHADAP KEPUASAN PELANGGAN (Studi Kasus Pada Pelanggan Waroeng Spesial Sambal Cabe Ijo 88 Nagoya Batam) - Daryadi D; Tibrani Tibrani; Ramon Zamora (EQUILIBIRIA, 2014)
Many businesses that have sprung up with similar characteristics, respectively. That customers were satisfied and did not move to another place, then the company must know the factors that affect customer satisfaction. Customer satisfaction can be created through price, quality products and quality service. In particular, this study discusses customer satisfaction waroeng special green chilli paste 88 Nagoya Batam. The researchers tested three independent variables, namely price, quality products and quality service that may affect satisfaction pelanggan.Tujuan this study was to determine the effect of three independent variables on customer satisfactionThis  study was  conducted  by  questionnaire  to  100  subscribers  special waroeng green chilli paste 88 Nagoya Batam obtained by using purposive sampling technique. Then the analysis of the data obtained in the form of quantitative and qualitative analysis. Quantitative analysis includes test validity and reliability, the classic assumption test, test multiple regression analysis (R2), the F test and t test. Qualitative analysis is the interpretation of the data obtained in the study and the results of data processing is carried out by providing information and explanation. The data that have met the test of validity, reliability, and classical assumption processed to produce a regression equation as follows Y = 2.907 + 0.018 X1 + 0.190 X2 + 0,544 X3 Results of this study indicate that all the independent variables in the test is positive and significant effect on customer satisfaction through the F test and t test while the number Adjusted Square (R2) 0.406 or 40.6%, this means the ability of a variable price, quality products and quality service in explain the purchase decision is 40.6%. remaining 59.4% is explained by other variables that are not included in this study.